INVESTIGATION OF THE VIBRATING TABLE PARAMETERS WITH A VIBRATOR LEVER FIXING - Коробко, Богдан; Коротич, Юрій (Modern engineering and innovative technologies, 2023)
The paper considers conducting laboratory studies to confirm the effectiveness of using the proposed design of the vibrating table with a vibration exciter lever attachment for small-sized concrete products under vibration compaction. Experiments were c